Securing wireless sensor networks with an efficient B+ tree-based key management scheme - Rasul, Khadija; Nuerie, Nujhat; Pathan, Al-Sakib Khan (Kohat University of Science and Technology (KUST), Pakistan, 2010)
Key management is an important issue in Wireless Sensor Networks (WSNs) for the secure communications among the nodes in the network. Based on the network settings and structure of the network, keys could be managed in various ways. Though there are quite a good number of key management schemes for WSNs, in this work, we present an enhanced heterogeneous tree based key management scheme for security of Wireless Sensor Networks (WSNs). Our scheme combines efficiently different key management techniques in each architecture level and also it has a dynamic key renewal process. Here, whenever a node is compromised, key renewal is done by one way hash functions and simple XOR operations. This combination gives the scheme good performance in terms of key storage overhead as well as resilience to the node capture attack. Our scheme shows relatively better performance compared to other existing heterogeneous schemes. Before presenting our scheme and its detailed analysis from multiple perspectives, we note down the related works to clarify this work’s background and motivation.